(untitled) - Lebra, Takie Sugiyama (Honolulu, 1974)
Addressing both the cultural context of behavior and the behavioral manifestations of culture, the 1974 edition of this text yielded a multifaceted yet remarkably integrated portrait of the Japanese. Within its pages classical stereotypes and seemingly contradictory behaviors were appraised, put into perspective, and made comprehensible.
Keywords: National characteristics, japanese